2022
DOI: 10.3390/ijerph19031530
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Remaining Life Expectancy at Age 60: A District-Level Analysis in Germany

Abstract: Remaining life expectancy at age 60 (in short: RLE) is an important indicator of the health status of a population’s elders. Until now, RLE has not been thoroughly investigated at the district level in Germany. In this study we analyzed, based on recent publicly available data (2015–2017), and for men and women separately, how large the RLE differences were in Germany across the 401 districts. Furthermore, we examined a wide range of potential social determinants in terms of their bivariate and multivariate (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 82 publications
2
3
1
Order By: Relevance
“…There is a general tendency to explain the existing regional differentials in Germany by the role of contemporary factors, notably by differences in socioeconomic conditions. 21 22 Contrary to this traditional view, the present analysis highlights the prominent role of past smoking behaviour.…”
Section: Discussioncontrasting
confidence: 76%
“…There is a general tendency to explain the existing regional differentials in Germany by the role of contemporary factors, notably by differences in socioeconomic conditions. 21 22 Contrary to this traditional view, the present analysis highlights the prominent role of past smoking behaviour.…”
Section: Discussioncontrasting
confidence: 76%
“…Our estimates of priority regarding influence of the analyzed factors on LEB in older age groups are similar to the results obtained in the study [23]. The authors examined remaining life expectancy 12 in various administrative districts in Germany by using twodimensional analysis.…”
Section: T a B L Esupporting
confidence: 85%
“…Educational attainment has been accepted as a crucial factor in explaining the differences in life expectancy among countries, because education can influence the life expectancy through many diverse channels such as economic growth and development, access to health-related information, employment of healthcare opportunities, planning horizon and risk perception at the subsequent period, raising the efficiency of health production (21)(22)(23)25). The extensive literature about the influence of educational attainment proxied by different education indicators on life expectancy has mainly reached a positive relationship between two variables (5,8,26,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Furthermore, educational attainment together with real GDP per capita have been suggested as the dominant factors for explaining the differences in life expectancy among the countries (8,21,23).…”
Section: Resultsmentioning
confidence: 99%
“…The first empirical studies on determinants of life expectancy have generally focused on the validity of Preston curve suggesting the relationship between GDP per capita and life expectancy. However, the influence of educational attainment, a crucial factor for the differences in life expectancy among the countries, on life expectancy has begun to be investigated as of 2000 s. The empirical studies have mainly represented the education by literacy, secondary and tertiary enrollment and education index and employed the regression analysis, cointegration analysis, and cluster analysis and have found that different education indicators have a positive influence on life expectancy in the countries with different development levels (5,8,26,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). However, Hazan (43)(44)(45) revealed an insignificant influence of educational attainment of life expectancy for some countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation